DNA-Assisted stabilization of graphene sheets and its applications as supercapacitors electrode - Albarqouni, Yasin M. Y.; M. Ali, Gomaa A.; Soon, Poh Lee; Rahim, Mohd-Hairul; Kwok, Feng Chong (Malaysian Institute of Chemistry, 2021)
The work reports on the formation of rGO/ssDNA composite by stabilizing rGO sheets in an aqueous solution containing ssDNA extracted from baker’s yeast culture. The as-formed rGO/ssDNA composite is verified using spectroscopic and microscopic techniques, including Fourier transform infrared (FTIR), Raman, and photoluminescence (PL) spectroscopies, and field emission scanning electron microscope (FESEM). Physical investigations show the successful stabilization of rGO suspension by ssDNA for more than a month without the rGO sheets precipitation. The highly charged backbone of ssDNA comprising phosphate groups, nucleic-bases, and sugar molecules contribute to the rGO stabilization and could be potential electrode material for charge storage supercapacitor. The electrochemical investigations confirm the electrochemical double-layer capacitance behavior of rGO/ssDNA composite in KOH electrolyte, where nearly 2-fold capacitance enhancement is observed compared to pure rGO.